Pemanfaatan Data Digital Terrain Model dan Metode Topographic Wetness Index untuk Pembuatan Peta Rawan Banjir Daerah Aliran Sungai (DAS) Kenali Besar Kota Jambi - Laswanto, Laswanto; Sunarti, Sunarti; Zuhdi, Mohd (Universitas Batanghari Jambi, 2025)
The aim of this research is to produce a map of flood-prone areas in the Kenali Besar watershed area by utilizing Digital Terrain Model (DTM) data using the Topographic Wetness Index method which is processed using Quantum GIS (QGIS) software. The results of this study revealed that 92.10% of the flood areas identified in this study were consistent with flood events that occurred in the field. Topographic Wetness Index analysis indicates that there are 347.0612 hectares (9.74% of the total area of the Kenali Besar watershed) that have the potential to experience flooding. This area is divided into three categories of vulnerability: 47.54 hectares with high vulnerability, 92.5 hectares with medium vulnerability, and 207.02 hectares with low vulnerability.